In situ phase transitional polymeric vaccines for improved immunotherapy. Issue 2 (27th August 2021) - Wang, Jie; Wang, Yi; Qiao, Shenglin; Mamuti, Muhetaerjiang; An, Hongwei; Wang, Hao
Abstract: Cancer vaccines have exhibited immense potential in cancer treatment. Through activating the host's immune system, vaccines stimulate extensive functional T cells to eliminate cancer. However, the therapeutic efficacy of cancer vaccines is limited by their inferior lymph node delivery and inadequate uptake of dendritic cells. Herein, we propose an in situ phase transitional strategy on vaccine manufacturing to maximally enhance lymph node drainage while ensuring adequate dendritic cell uptake. The phase transitional vaccines, with dynamic size modulation property, retain a small size (24.4 ± 3.1 nm) during lymph node draining then transform into larger particles (483.0 ± 41.6 nm) on-site by external signal input. Results show that this strategy induced rapid and robust immune response in a mouse melanoma tumor model. Furthermore, a stronger humoral immune response was observed in mice when immunized with MHC-II restricted antigen, which demonstrated that lymph node-targeted cancer vaccine delivery could be effectively manipulated through dynamic size modulation. Abstract : By analyzing the unique features of the vaccine delivery process, a new strategy is proposed to improve both lymph node drainage and dendritic cell endocytosis through dynamic size modulation.